2020
DOI: 10.1038/s41598-020-71433-9
|View full text |Cite
|
Sign up to set email alerts
|

TNF genetic polymorphism (rs1799964) may modify the effect of the dietary inflammatory index on gastric cancer in a case–control study

Abstract: The inflammatory process is known to increase the risk of gastric carcinogenesis, and both genetic and dietary factors are associated with inflammation. In the present study of 1,125 participants (373 cases and 752 controls), we determined whether the dietary inflammatory index (DII) is associated with the risk of gastric cancer (GC) and investigated whether a TNF polymorphism (rs1799964) modifies this association. Semi-quantitative food frequency questionnaire derived data were used to calculate the DII score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“… 32 Furthermore, a case-control study of 1125 people found that the DII was associated with cancer risk, and the impact of DII on stomach cancer risk varied depending on TNF genotype. 33 Our research findings align with the aforementioned results, indicating that a pro-inflammatory diet can be considered a risk factor for stomach cancer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 32 Furthermore, a case-control study of 1125 people found that the DII was associated with cancer risk, and the impact of DII on stomach cancer risk varied depending on TNF genotype. 33 Our research findings align with the aforementioned results, indicating that a pro-inflammatory diet can be considered a risk factor for stomach cancer.…”
Section: Discussionsupporting
confidence: 90%
“…[26][27][28][29] DII has been found to be particularly relevant to stomach diseases. [30][31][32][33] A cohort study in Korea reported that individuals in the highest quartile of DII score showed a 1.22-fold higher risk of incident stomach diseases compared to those in the lowest quartile. 30 Additionally, an Italian case-control study revealed a weak association between a pro-inflammatory diet and an increased risk of stomach cancer, as compared to an anti-inflammatory diet.…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression of inflammatory genes was observed in females than in males due to sex hormones (45) . Thus, different eating habits and sex hormones may account for the difference in the interactive effect between males and females (46) . This interaction should be elucidated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The genotyping and quality control processes have been described in previous studies [ 26 , 27 , 28 ]. Extraction of genomic DNA was performed using peripheral blood leukocytes.…”
Section: Methodsmentioning
confidence: 99%